IMMUNOHISTOCHEMICAL LOCALIZATION OF HNF4? IN THE CHOROID PLEXUS OF THE RABBIT VENTRICLES WITH CLINICAL IMPLICATION (Iraqi Journal of Medical Sciences, 2016)
Background:The choroid plexuses are composed of highly differentiated epithelial cells in with connective tissue and permeable capillaries among them. These cells connected by tight junction to form the blood –CSF-barrier that plays important role in protection of CNS. HNF4? is transcription factor of many drugs transporter proteins and known as nuclear subfamily 2 group alpha encoded by HNF4 alpha gene can be found in the liver, pancreas, intestine, brain and recently in epithelial cell of choroid plexuses.Objectives:To evaluation the HNF4? intensity and localization of the choroid plexus in the lateral and forth ventricles of the rabbit.Methods:Choroid plexuses of lateral and forth ventricles of 30 adult male rabbits were studied by morphological and immunohistochemical evaluation of HNF4? in theses ventricles that play role in regulation of drugs transporters and drugs metabolism in B-CSF-B.Results: Histological method showed little different features by subjective examination between various localizations of the choroid plexuses. The immunohistochemical activity of HNF4? was different between lateral and forth ventricle where the IHC positivity is more in the lateral ventricle (0.067±0.029) than forth ventricle (0.032 ±0.018) and this results is statistically significant.Conclusion:The choroidal cells of lateral ventricle showed more IHC activity of HNF4? and might indicate targeting of many drug transporters proteins, metabolites and eliminate of toxic compounds from brain tissues.Key word:Choroid plexuses, HNF4? in lateral ventricle, drug transporter across the blood brain barrier.
Keywords: Choroid plexuses; HNF4 in lateral ventricle; drug transporter across the blood brain barrier